EP.WE.629The effect of different anaesthetic agents in postsurgical inflammatory response in thoracic surgery: a systematic review. (28th October 2021) - Aquilina, Julian; Geropoulos, Georgios; Loufopoulos, Ioannis; Gupte, Anaya; Mitsos, Sofoklis; Panagiotopoulos, Nikolaos
Abstract: Aims: Post-operative systemic inflammatory reaction is part of the stress response caused by major thoracic surgery. Different anaesthetic agents used affect different immunological phenomena. This systematic review evaluates the impact of anaesthetic agents on the immunological profile and the associated clinical significance. Methods: A systematic review of MEDLINE, EMBASE and Cohrane databases to explore how different anaesthetic agents affect post-operative inflammatory response. Results: A total of nine studies were included in our analysis. Peri-operative use of dexmedetomidine, propofol, sevoflurane, isoflurane, ropivacaine, sufentanil, naloxone and clonidine were compared, based on their effect on the systemic release of inflammatory markers. Variance on the levels of the circulating inflammatory molecules such as interleukins, interferon-γ, tumor necrosis factor a and on the cellular response including natural killer, CD4 and CD8 T cells, were observed among different anaesthetic agents. Conclusions: Inflammation improves immunity and regenerative cell recruitment, however excessive responses can lead to delayed wound healing, organ dysfunction and increased morbidity and mortality. There is still uncertainty regarding the role of immune changes on clinical outcomes of patients undergoing thoracic surgery, and more research is needed to explore other immunological effects related to anaesthetic agents.